University Funding Policies: Buildings or Citizens? - Pier-André Bouchard St-Amant (Queen's University, Department of Economics, 2013)
Governments tend to fund universities based on the number of registered students and lump sum transfers. Such policy induces universities to compete for recruiting students, diverting money away from funds devoted to teaching. I show this degradation of quality increases with the degree to which universities compete for the same students. I suggest a policy that achieves the social optimum for any given level of funding. This policy shows that a university's funding rules should not be solely based on its enrollement, but also on the enrollment in competing universities.
Keywords: H52; I23; I28; 330; University; Funding Policies; Decentralized Decisions